FAKTOR-FAKTOR YANG MEMPENGARUHI PENGGUNAAN FINTECH LENDING PADA GENERASI MILENIAL - Tirta Dewi, Ni Putu Aprilianti; Yadnyana, I Ketut; Yasa, Gerianta Wirawan; Wirajaya, I Gde Ary (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.11.NO.05.TAHUN.2022, 2022)
Loan-based fintech systems (fintech lending) allow users to apply for loans online and provide small loan interest, even some fintech lending frees users from loan interest. This study aims to obtain empirical evidence regarding the determinants of the use of fintech lending in the millennial generation amid the increasingly rapid development of digital technology-based information systems in various fields. This study uses a quantitative approach. The data used in this study is primary data, namely through a survey method to respondents who are millennials in the province of Bali with a total of 400 respondents spread across nine regencies/cities in the province of Bali obtained by purposive sampling technique. Furthermore, the data obtained were processed using the SEM-PLS statistical tool. The results show that the perceived benefits of fintech lending system users, economic benefits, transaction speed, and convenience have a positive effect on the use of fintech lending. Meanwhile, the perception of risk perceived by fintech lending users, financial risk, security risk, and operational risk has a negative effect on the use of fintech lending. The results of this study confirm the Theory of Reasoned Action (TRA) in terms of attitudes towards individual behavior on the influence of subjective norms and user acceptance of an information system that will affect individual interest in using information technology.